Enhanced myogenesis through lncFAM-mediated recruitment of HNRNPL to the MYBPC2 promoter. Issue 22 (19th December 2022) - Chang, Ming-Wen; Yang, Jen-Hao; Tsitsipatis, Dimitrios; Yang, Xiaoling; Martindale, Jennifer L; Munk, Rachel; Pandey, Poonam R; Banskota, Nirad; Romero, Brigette; Batish, Mona; Piao, Yulan; Mazan-Mamczarz, Krystyna; et al.
Abstract: The mammalian transcriptome comprises a vast family of long noncoding (lnc)RNAs implicated in physiologic processes such as myogenesis, through which muscle forms during embryonic development and regenerates in the adult. However, the specific molecular mechanisms by which lncRNAs regulate human myogenesis are poorly understood. Here, we identified a novel muscle-specific lncRNA, lncFAM71E1-2:2 ( lncFAM ), which increased robustly during early human myogenesis. Overexpression of lncFAM promoted differentiation of human myoblasts into myotubes, while silencing lncFAM suppressed this process. As lncFAM resides in the nucleus, chromatin isolation by RNA purification followed by mass spectrometry (ChIRP-MS) analysis was employed to identify the molecular mechanisms whereby it might promote myogenesis. Analysis of lncFAM -interacting proteins revealed that lncFAM recruited the RNA-binding protein HNRNPL to the promoter of MYBPC2, in turn increasing MYBPC2 mRNA transcription and enhancing production of the myogenic protein MYBPC2. These results highlight a mechanism whereby a novel ribonucleoprotein complex, lncFAM -HNRNPL, elevates MYBPC2 expression transcriptionally to promote myogenesis.